Art therapy for people with mental illness: overview of the evidence from empirical research on the effectiveness of the treatment / Salmi Razali - Razali, Salmi (Faculty of Art and Design, 2021)
Art therapy is a technique that uses creative expression to help people explore emotions, develop self-awareness and insight on life experience, overcome stress, increase self-esteem, and enhance social skills. Lately, there has been a growing interest among mental health professionals to prescribe art therapy to people with mental illness. It is crucial that the treatment for people with mental illness is informed by valid evidence, not merely anecdotal opinions, personal testimony nor superstition. This article aims to review the empirical evidence and discuss the question of whether art therapy is beneficial for an individual with mental illness. Articles published between 2000 until 2021were retrieved from search engines including EMBASE, Medline and PsychINFO. A total of 55 empirical studies were reviewed. The majority of the review evaluating the effectiveness of art therapy suggested that most studies are limited by methodological issues including the small number of subjects, poor protocols of the intervention and subjective outcome measures. Nonetheless, current empirical evidence suggests that art therapy may be beneficial as a means for venting out the negative repressed emotions or trauma, improve communication, enhance interpersonal relationships and increase support system. Most mental health professionals recommend patients with mental illness are treated with proven effective psychotherapies (for mild to moderate cases), with additional pharmacotherapy (for moderate to severe illness), and art therapy serves as supplementary to these conventional treatments. Art therapy may be beneficial as an adjunct treatment for mental illnesses. More evidence is required to show the effectiveness of art therapy.